2020
DOI: 10.9770/jesi.2020.8.1(20)
|View full text |Cite
|
Sign up to set email alerts
|

Perceived influence of corporate social responsibility on consumer loyalty: the role of ethical ideology

Abstract: This study explored how different types of perceived corporate social responsibility serve to affect customer loyalty, and how consumer ethical ideologies affect perceived corporate social responsibility. The empirical research analysis reveals that respondents are more often characterised by an ethical ideology of idealism, and that they are most aware of any corporate social responsibility (CSR) that is consumer-orientated. In addition, it has been found that the perceived CSR, which focuses on the public, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…Institutional theory Social institutions are imperative to establish a moral code for organizations [45,46] Stewardship theory CSR is regarded as a set of moral values to be practiced in businesses without considering its relationship with performance [47] Agency theory CSR is an outcome of self-serving behavior of management at shareholders' expense [48] Stakeholder theory CSR is principally the outcome of developing associations with actors/entities which are affected or can affect the businesses [49] Resource based view CSR is regarded as a potential capability that can generate competitive advantage [50] The present study uses the theoretical lens of resource-based view (RBV) and institutional theory, which are referred to underpinning theories for present research. It is logical to use these theoretical lenses simultaneously as the previous literature confirms this approach [51][52][53].…”
Section: Theory Descriptionmentioning
confidence: 99%
“…Institutional theory Social institutions are imperative to establish a moral code for organizations [45,46] Stewardship theory CSR is regarded as a set of moral values to be practiced in businesses without considering its relationship with performance [47] Agency theory CSR is an outcome of self-serving behavior of management at shareholders' expense [48] Stakeholder theory CSR is principally the outcome of developing associations with actors/entities which are affected or can affect the businesses [49] Resource based view CSR is regarded as a potential capability that can generate competitive advantage [50] The present study uses the theoretical lens of resource-based view (RBV) and institutional theory, which are referred to underpinning theories for present research. It is logical to use these theoretical lenses simultaneously as the previous literature confirms this approach [51][52][53].…”
Section: Theory Descriptionmentioning
confidence: 99%
“…These are just some of the fundamental questions that the company must ask itself in order to define the strategic lines aimed at pursuing a correct reformulation of the business model. The answers to these questions come in part from the monitoring and control of the performance achieved, which must take place in a constant manner and always keeping in mind that the evolution today must take place in a "responsible" and "sustainable" key [31].…”
Section: Psychosocial Educational and Economic Impacts Of Covid-19mentioning
confidence: 99%
“…As for the studies on the correlation between CSR and consumer attitude, Ramesh et al [41] found that after people learn about CSR-related activities, their perceptions change and they form positive brand identification, which leads to positive attitudes and impressions of the brand. This indicates that consumers will identify with, and develop positive attitudes toward companies that fulfill their commitment to CSR, and will actively support socially responsible brands [40,[42][43][44].…”
Section: Corporate Social Responsibilitymentioning
confidence: 99%